2016
DOI: 10.1186/s12884-016-0884-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hepatitis B virus carrier status and pregnancy outcomes: a prospective cohort study

Abstract: BackgroundInfection with hepatitis B virus (HBV) in pregnant women may be a threat for both mothers and fetuses. This study was performed to explore the impact of maternal HBV carrier status on pregnancy outcomes.MethodsWe conducted a prospective cohort study at the Obstetrics & Gynecology Hospital of Nantong University between January 1, 2012 and September 30, 2015. A consecutive sample of 21,004 pregnant women, 513 asymptomatic HBV carriers and 20,491 non-HBV controls, was included in this study. The main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
108
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 28 publications
11
108
2
2
Order By: Relevance
“…The lowest reported prevalence of HBsAg positivity was 0.09%, and the highest was 11.6% . Eleven studies reported prevalence's higher than 3.61%, as opposed to nine with lower than 3.61% . The other three studies did not include this information …”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The lowest reported prevalence of HBsAg positivity was 0.09%, and the highest was 11.6% . Eleven studies reported prevalence's higher than 3.61%, as opposed to nine with lower than 3.61% . The other three studies did not include this information …”
Section: Resultsmentioning
confidence: 94%
“…After screening the title and abstract, 88 reports were potentially eligible. Finally, 23 studies, including 21 full reports and two conference abstracts published after 1999, were eligible after full‐text screening . The flow chart of included studies is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations